An Introduction to Some Common and Charismatic Florida Spiders - E. C. Powell; L. A. Taylor; Samm Wehman Epstein (EDIS)
Florida has a rich diversity of spiders that vary greatly in body shape, size, color, hunting strategy, and habitat. While spiders are often feared, they are generally non-aggressive and provide essential ecosystem services, such as controlling pest insects in homes, gardens, and agricultural crops. This publication highlights some of the most commonly encountered spiders in Florida and some less common, but particularly charismatic, groups. The publication provides information on species biology along with images and descriptions for spiders across 15 families. Accompanying the publication is a downloadable educational coloring book focused on spiders, providing a creative way for people of all ages to appreciate the beauty and intrigue of spiders.